The Old Man and the Sea - Hemingway, Ernest, 1899-1961.; Sutherland, Donald, 1935-2024 (London, UK Arrow Books, 2004)
The story of an old Cuban fisherman, down on his luck, and his supreme ordeal, a relentless, agonizing battle with a giant marlin far out in the Gulf Stream.
Unabridged.
With tracks every 3 minutes for easy book marking.
Compact discs.
Narrated by Donald Sutherland.
Keywords: Fishers -- Cuba -- Fiction; Older men -- Cuba -- Fiction; Friendship -- Fiction; Fishers -- Cuba -- Fiction; Marlin fishing -- Cuba -- Fiction; Courage in men -- Fiction; Metaphorical tales; Cuba -- Fiction; Bildungsromans; Allegories; Audiobooks; Fiction